Pengembangan Kapasitas Pelayan Gereja dalam Mengimplementasikan Amanat Agung melalui Seminar Pengabdian kepada Masyarakat oleh STT Kristus Alfa Omega Semarang - Wahyudi Sri Wijayanto; Didasgil SI Taneo; Sunarti (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This Community Service Program aimed to enhance the capacity of church ministers in implementing the Great Commission through a seminar and mentoring program organized by STT Kristus Alfa Omega Semarang. The program began with a needs assessment conducted at Filadelfia Community Church, GBT Kristus Alfa Omega Boja, and GBI Jatisari Semarang to identify ministry challenges and serve as the basis for developing the seminar materials. The methods employed included observation, interviews, interactive seminars, group discussions, case studies, and mentoring for ministry program implementation. The findings indicate an improvement in participants' understanding of the theological foundation of the Great Commission, discipleship, servant leadership, and contextual ministry strategies in a pluralistic society. Participants were also able to formulate follow-up action plans tailored to the needs of their respective churches. Furthermore, the program strengthened collaboration between the theological institution and local churches in empowering church ministers and promoting sustainable discipleship-based ministry. This community service model has the potential to be replicated in other churches with similar characteristics.